PENDAMPINGAN DALAM PEMBERDAYAAN TANAH WAKAF DESA PUTAT LOR - Muyassaroh; M. Saiful Islam (Lembaga Penelitian, Pengembangan dan Pengabdian Kepada Masyarakat (LP3M), 2021)
This community service is carried out in the form of Islamic philanthropy which focuses on legalizing and empowering waqf land. The legalized waqf land is in the form of non-productive waqf as well as several prayer rooms (musala) located in the area of Putat Lor village, Krajan, Gondanglegi, in Malang district. This waqf is trying to be assisted in the legalization process by carrying out the three-stage of